2014
DOI: 10.1002/ase.1510
|View full text |Cite
|
Sign up to set email alerts
|

A meta‐analysis of the educational effectiveness of three‐dimensional visualization technologies in teaching anatomy

Abstract: Many medical graduates are deficient in anatomy knowledge and perhaps below the standards for safe medical practice. Three-dimensional visualization technology (3DVT) has been advanced as a promising tool to enhance anatomy knowledge. The purpose of this review is to conduct a meta-analysis of the effectiveness of 3DVT in teaching and learning anatomy compared to all teaching methods. The primary outcomes were scores of anatomy knowledge tests expressed as factual or spatial knowledge percentage means. Seconda… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

16
224
3
4

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 239 publications
(270 citation statements)
references
References 83 publications
16
224
3
4
Order By: Relevance
“…55 Similarly, Yammine and Violato showed that the pedagogical use of 3DTV yields better results when compared to their 2D counterparts, regarding learning factual Anatomy, with substantial educational benefits on spatial Anatomy knowledge. 56 Also, this learning perspective might contribute to improving the connection and feedback between teacher and students, for instance through social media network 30,31 and, subsequently, cause an impact in learner's performance. 57 The introduction of computer integrated systems in Anatomy Education lends itself to a better analysis of the teaching-learning-assessment dimensions, at the same time, delivering new environments to that processes.…”
Section: 50mentioning
confidence: 99%
“…55 Similarly, Yammine and Violato showed that the pedagogical use of 3DTV yields better results when compared to their 2D counterparts, regarding learning factual Anatomy, with substantial educational benefits on spatial Anatomy knowledge. 56 Also, this learning perspective might contribute to improving the connection and feedback between teacher and students, for instance through social media network 30,31 and, subsequently, cause an impact in learner's performance. 57 The introduction of computer integrated systems in Anatomy Education lends itself to a better analysis of the teaching-learning-assessment dimensions, at the same time, delivering new environments to that processes.…”
Section: 50mentioning
confidence: 99%
“…Students describe CAL anatomy instruction as enjoyable [21,22,23] and accept computer-based interactive technology as an effective approach in conveying anatomical information [24,25]. Advantages of supplementing traditional methods with CAL include novel anatomic perspective, increased portability and longevity, and increased standardization [26,27]. …”
Section: Introductionmentioning
confidence: 99%
“…Then, in the clinical years of the medical curriculum this concept will need to be retained and strengthened, since the anatomical variability plays an essential role in clinical activity (Sañudo 2003;Yammine and Violato 2015), markedly influencing medical choices and, above all, surgical practice (Marcos 2000).…”
Section: Discussionmentioning
confidence: 99%